High-efficiency load modulation power amplifiers for wireless communications - Wang, Zhancang (Artech House microwave library., 2017)
Includes practical and cutting-edge insight, this book presents a complete and systematic overview of the practical design considerations of radio frequency (RF) high efficiency load modulation power amplifiers (PA) for modern wireless communications for 4G and beyond. --